A method for preparing carbon-coated sodium ferric sulfate material

The carbon-coated sodium iron sulfate material is prepared by the emulsion method, which solves the problems of low yield and poor material stability in the existing technology, achieves high yield and excellent electrochemical performance, and is suitable for sodium ion batteries.

CN117613232BActive Publication Date: 2025-09-23SINOSTEEL ANHUI TIANYUAN TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311617003.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-30
Publication Date
2025-09-23
Estimated Expiration
2043-11-30

AI Technical Summary

Technical Problem

The yield of existing carbon-coated sodium ferric sulfate materials is not high enough, and the materials are easy to absorb water and be oxidized, resulting in poor cycle performance.

Method used

Carbon-coated sodium ferric sulfate material was prepared by emulsion method. Graphene was used as carbon material to carry out emulsion polymerization with ferrous sulfate heptahydrate and anhydrous sodium sulfate. After freeze-drying and low-temperature vacuum drying, it was calcined to prepare graphene-coated sodium ferric sulfate material.

Benefits of technology

The material yield is increased to 92-95%, the graphene coating is uniform, the conductivity is good, it is not easy to absorb water, it is not easy to be oxidized, it has good long-term cycle stability, and it has excellent electrochemical properties, making it suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117613232B_ABST
    Figure CN117613232B_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a carbon-coated sodium ferric sulfate material, relates to the technical field of sodium ion battery positive electrode material preparation, and aims to solve the problem of low yield in existing methods. The method comprises the following steps: dropping an emulsifier into pure water and dispersing the mixture evenly; adding ferrous sulfate heptahydrate and anhydrous sodium sulfate powder and dispersing the mixture until the solid powder is completely dissolved; adding graphene and dispersing the mixture evenly; heating the mixture to a preheating temperature and adding a polymerization initiator; dropping acrylic acid; heating the mixture to a reaction temperature, keeping the temperature until the reaction is sufficient, and then cooling the temperature to room temperature; freeze-drying the mixture, and then vacuum drying the mixture at low temperature after solidification to obtain a solid; grinding the mixture, calcining the mixture, and then grinding the mixture again to obtain a carbon-coated sodium ferric sulfate product with a yield of not less than 92%. The method has simple process steps and is easy to operate, has low raw material cost, high product yield, low production cost, and excellent electrochemical performance of the prepared carbon-coated sodium ferric sulfate material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of preparation of positive electrode materials for sodium ion batteries, and in particular to a method for preparing a carbon-coated sodium ferric sulfate material. Background Art

[0002] Energy is fundamental to human development. However, overexploitation of traditional fossil resources is not only leading to their depletion but also causing severe environmental pollution. Therefore, green, environmentally friendly, and sustainable electrochemical energy storage, as a key branch of various energy storage technologies, is attracting increasing attention. Among existing energy storage battery systems, lithium-ion batteries (LIBs) are favored by the market due to their flexible material systems and rapid technological updates. However, unresolved issues such as high battery costs, limited lithium-ion resources, and relatively poor safety have hindered the widespread adoption of this technology. Consequently, many researchers have turned their attention to sodium-ion batteries (SIBs). Sodium and lithium are metallic elements of the same family, sharing similar physical and chemical properties. Furthermore, sodium is abundant in nature, with an abundance of approximately 2.64% in the Earth's crust, making it relatively easy to extract. SIBs are significantly cheaper than LIBs and, more importantly, pose no long-term threat to natural resources. Therefore, using sodium instead of lithium to develop SIBs holds great promise for broad application.

[0003] The main purpose of sodium ion battery cathode materials is to provide channels or spaces for repeated insertion and removal of sodium ions. From the introduction of sodium ions to the present, the research and development and preparation of sodium ion battery cathode materials are one of the important technologies that determine whether high power density and high energy density sodium batteries can be developed. Common sodium ion cathode materials include layered metal oxides Na x MO2 (M = Co, Ni, Fe, Mn, V, Ti, etc.), polyanion compounds NaFePO4, NaMnPO4, Na3V2(PO4)3, Prussian blue analogues Na2Fe[Fe(CN)6], Na2Mn[Fe(CN)6] and Na2Ni[Fe(CN)6]. Considering that most of the existing sodium ion battery positive electrode materials are transition metal oxides, the lattice of the oxide has a relatively large restriction on sodium ions, resulting in poor electrochemical performance. The common polyanion material sodium iron sulfate has the advantages of low raw material cost, simple preparation process and high operating voltage. In the existing coating method, the in-situ organic carbon source has poor conductivity and the inorganic carbon source coating is not uniform, which makes the material easy to absorb water and be easily oxidized, and ultimately leads to poor cycle performance and other problems.

[0004] The invention patent application with publication number CN116093292A, entitled "A method for preparing a carbon-coated sodium ferric sulfate material, a carbon-coated sodium ferric sulfate material, and a battery," discloses a method for obtaining carbon-coated sodium ferric sulfate by mixing a surfactant with carbon nanotubes, adding the mixture to a raw material solution, stirring, and performing solid-liquid separation, drying, and calcining. This method is relatively simple, and provides a relatively uniform coating, good conductivity, and is not easily absorbed by water or oxidized. However, this method actually utilizes the action of CTAB and a metal salt to precipitate ferrous sulfate heptahydrate and anhydrous sodium sulfate, requiring a saturated micelle concentration to cause precipitation. Therefore, although the amount of CTAB does not affect the product performance, this method requires the addition of a relatively large amount of CTAB to obtain the product, and the yield is also relatively low, indirectly increasing the preparation cost. Summary of the Invention

[0005] The object of the present invention is to provide a method for preparing a carbon-coated sodium ferric sulfate material to solve the problem that the yield of the existing method is not high enough.

[0006] To achieve the above object, the present invention provides the following technical solution: a method for preparing a carbon-coated sodium ferric sulfate material, comprising the following specific steps:

[0007] S1. Add the emulsifier dropwise into pure water and disperse evenly;

[0008] S2. Add ferrous sulfate heptahydrate and anhydrous sodium sulfate powder to the mixture obtained in S1 and disperse until the solid powder is completely dissolved;

[0009] S3. Graphene is added to the mixture obtained in S2 and dispersed evenly;

[0010] S4. The mixture obtained in S3 is heated to the preheating temperature and a polymerization initiator is added;

[0011] S5. Acrylic acid was added dropwise to the mixture obtained in S4;

[0012] S6. The mixture obtained in S5 was heated to the reaction temperature and kept warm until the reaction was fully cooled to room temperature;

[0013] S7. The mixture obtained in S6 was freeze-dried and dried under vacuum at low temperature after solidification to obtain a solid;

[0014] S8. Grind the solid obtained in S7, calcine it, and then grind it again to obtain a carbon-coated sodium ferric sulfate product.

[0015] Preferably, in the above step S1, the mass ratio of emulsifier to water is (0.0004-0.001):1.

[0016] Preferably, in the above step S2, the mass ratio of ferrous sulfate heptahydrate to water is (0.22-0.25):1, and the molar ratio of ferrous sulfate heptahydrate to anhydrous sodium sulfate is 1:(0.5-2).

[0017] Preferably, in the above step S3, the type of graphene is one or more of single-layer graphene, double-layer graphene, and thick-layer graphene, and the mass ratio of graphene to ferrous sulfate heptahydrate is (0.02-0.08):1.

[0018] Preferably, in the above step S4, the preheating temperature is 60-70° C., and the initiator is one of ammonium persulfate and potassium persulfate, and the mass ratio of ammonium persulfate to the emulsifier is 1:(2-3).

[0019] Preferably, in the above step S5, acrylic acid is added dropwise using a peristaltic pump, the speed of the peristaltic pump is controlled at 3-5 rpm, and the mass ratio of acrylic acid to water is (0.01-0.015):1.

[0020] Preferably, in the above step S6, the reaction temperature is 75-85° C., and the insulation time is 0.8-1.2 h.

[0021] Preferably, in the above step S7, the freeze-drying temperature is -60 to -40°C, and the low-temperature vacuum drying treatment time is 18 to 24 hours.

[0022] Preferably, in the above step S8, a tubular furnace is used for calcination, the calcination temperature is 300-360° C., and the calcination time is 5-7 hours.

[0023] Preferably, the yield of the carbon-coated sodium ferric sulfate product obtained by the above preparation method is 92-95%, and the graphene is evenly coated on the surface of the sodium ferric sulfate, and the microscopic morphology is spherical.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] 1. The preparation method of the carbon-coated sodium ferric sulfate material uses an emulsion method instead of traditional pure water as a liquid phase to carbon-coat the sodium ferric sulfate, so that the sodium ferric sulfate can be completely dissolved while the graphene powder can be more evenly dispersed; the carbon material used is a graphene material with high conductivity and negative charge, and a polymerization reaction is carried out in the emulsion to synthesize polyacrylic acid. The presence of carboxyl groups in the polymer can effectively improve the binding ability of sodium ferric sulfate and graphene, and can gradually enhance the interaction force between graphene and sodium ferric sulfate during the acrylic emulsion polymerization process. Moreover, due to the influence of the steric hindrance of the polymer, the graphene-coated sodium ferric sulfate crystals after drying have smaller size, more regular morphology, uniform coating, good conductivity, low water absorption, low oxidation, and good long-term cycle stability.

[0026] 2. The preparation method of the carbon-coated sodium ferric sulfate material has simple and easy-to-operate process steps, low raw material cost, high product yield, and low production cost. The prepared carbon-coated sodium ferric sulfate material has excellent electrochemical properties, can meet the application requirements of sodium ion batteries, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a microscopic morphology image of the graphene-coated sodium ferric sulfate product in Example 1 of the present invention, taken using a scanning electron microscope (SEM).

[0028] Figure 2 This is the XRD diffraction pattern of the graphene-coated sodium ferric sulfate product in Example 1 of the present invention.

[0029] Figure 3 This is the 0.1C charge-discharge capacity test curve of the sample in Example 1 of the present invention. DETAILED DESCRIPTION

[0030] A method for preparing a carbon-coated sodium ferric sulfate material comprises the following specific steps:

[0031] S1. The emulsifier is added dropwise to pure water and dispersed evenly. Preferably, the mass ratio of the emulsifier to water is (0.0004 to 0.001): 1. There is no specific requirement for the type of emulsifier. Further, optionally, the dispersion speed may be 120 to 160 rpm.

[0032] S2. Add ferrous sulfate heptahydrate and anhydrous sodium sulfate powder to the mixed solution obtained in S1 and disperse until the solid powder is completely dissolved, wherein the mass ratio of ferrous sulfate heptahydrate to water is preferably (0.22 to 0.25):1, and the molar ratio of ferrous sulfate heptahydrate to anhydrous sodium sulfate is preferably 1:(0.5 to 2);

[0033] S3. Graphene is added to the mixed solution obtained in S2 and dispersed evenly. Optionally, the graphene is one or more of single-layer graphene, double-layer graphene, and thick-layer graphene (ie, multilayer graphene). In addition, the mass ratio of graphene to ferrous sulfate heptahydrate is preferably controlled within a range of (0.02 to 0.08):1.

[0034] S4. The mixture obtained in S3 is heated to a preheating temperature, generally 60 to 70 ° C, and a polymerization initiator is added. For reference, the initiator can be ammonium persulfate or potassium persulfate, and the mass ratio of the initiator to the emulsifier can be 1: (2 to 3);

[0035] S5. Acrylic acid is added dropwise to the mixture obtained in S4. It is recommended to use a peristaltic pump for dropwise addition. The peristaltic pump speed can be controlled at 3 to 5 rpm, the dropwise addition rate can be further preferably 1.5 to 2 ml / min, and the mass ratio of acrylic acid to water can be further preferably (0.01 to 0.015):1; of course, the dropwise addition of acrylic acid can also be carried out by other means, such as manually or with an infusion pump;

[0036] S6. The mixture obtained in S5 is heated to the reaction temperature and kept warm until the reaction is sufficient and then cooled to room temperature; in a preferred embodiment, the reaction temperature is controlled to 75 to 85 ° C and the holding time is 0.8 to 1.2 h;

[0037] S7. The mixture obtained in S6 is freeze-dried and then solidified by low-temperature vacuum drying to obtain a solid. The drying process should not be heated to avoid destroying the structure of the latex particles in the emulsion. In a preferred embodiment, the freeze-drying temperature is -60 to -40 ° C, and the low-temperature vacuum drying process time is 18 to 24 h.

[0038] S8. Grind the solid obtained in S7 and calcine it, then grind it again to obtain a carbon-coated sodium ferric sulfate product with a yield of up to 92 to 95%; wherein the calcination can be carried out in a tubular furnace, and more preferably, the calcination temperature is 300 to 360° C. and the calcination time is 5 to 7 hours.

[0039] Example 1:

[0040] Add 0.25g of emulsifier to 500mL of pure water and disperse evenly at a speed of 130rpm. Add 111.2g of ferrous sulfate heptahydrate and 56.8g of sodium sulfate to the mixture. Once completely dissolved, add 3g of single-layer graphene. Then, raise the temperature of the mixture to 60°C, add 0.15g of potassium persulfate, start the peristaltic pump, and add 5.5g of acrylic acid dropwise at 3.5rpm. After the addition is complete, raise the temperature of the mixture to 78°C and maintain it for 0.8h to allow emulsion polymerization to proceed.

[0041] After the completion, the temperature was naturally lowered to room temperature and then placed at -40°C for low temperature solidification. After the completion, the low temperature vacuum drying was carried out and the obtained solid was taken out and ground after 18 hours. The solid was placed in a tube furnace for calcination at a temperature of 340°C and a calcination time of 6 hours. The obtained solid was ground and recorded as Example 1. The solid was subjected to SEM and XRD examination. Figure 1 It can be seen that graphene is evenly coated on the surface of sodium iron sulfate and is in a relatively regular spherical shape without obvious agglomeration; Figure 2 As shown in the figure, the sample has high peak intensity and few impurity peaks, indicating that there are fewer impurities in the synthetic product.

[0042] Example 2:

[0043] Add 0.7g of emulsifier to 1000mL of pure water and disperse evenly at a speed of 160rpm. Add 236.3g of ferrous sulfate heptahydrate and 60.4g of sodium sulfate to the mixture. Once completely dissolved, add 16.54g of thick-layer graphene. Then, raise the temperature of the mixture to 65°C, add 0.45g of potassium persulfate, start the peristaltic pump, and add 13.7g of acrylic acid dropwise at 3.5rpm. After the addition is complete, heat the mixture to 81°C and maintain for 1h to allow emulsion polymerization.

[0044] After completion, the temperature naturally dropped to room temperature and was placed at -50°C for low-temperature solidification. After completion, the temperature was vacuum dried at low temperature and kept for 22 hours. The obtained solid was taken out and ground, and then placed in a tubular furnace for calcination at a temperature of 340°C for 5.5 hours. The obtained solid was ground and recorded as Example 2.

[0045] Example 3:

[0046] Add 0.42g of emulsifier to 700mL of pure water and disperse evenly at a speed of 140rpm. Add 161.7g of ferrous sulfate heptahydrate and 104.1g of sodium sulfate to the mixture. Once completely dissolved, add 11.39g of single-layer graphene. Then, raise the temperature of the mixture to 68°C, add 0.2g of ammonium persulfate, start the peristaltic pump, and add 8.4g of acrylic acid dropwise at 4.5rpm. After the addition is complete, raise the temperature of the mixture to 84°C and maintain it for 1.2h to allow emulsion polymerization to proceed.

[0047] After completion, the temperature naturally dropped to room temperature and was placed at -50°C for low-temperature solidification. After completion, the temperature was vacuum dried at low temperature and kept for 24 hours. The obtained solid was taken out and ground, and then placed in a tubular furnace for calcination at a temperature of 360°C for 6.5 hours. The obtained solid was ground and recorded as Example 3.

[0048] Example 4:

[0049] Add 0.3g of emulsifier to 300mL of pure water and disperse evenly at a speed of 125rpm. Add 67.5g of ferrous sulfate heptahydrate and 52.6g of sodium sulfate to the mixture. Once completely dissolved, add 3.4g of bilayer graphene. Then, raise the temperature of the mixture to 63°C, add 0.1g of ammonium persulfate, start the peristaltic pump, and add 4.5g of acrylic acid dropwise at 3rpm. After the addition is complete, raise the temperature of the mixture to 76°C and maintain it for 1h to allow emulsion polymerization.

[0050] After completion, the temperature naturally dropped to room temperature and then was placed at -55°C for low-temperature solidification. After completion, the mixture was dried in a low-temperature vacuum and kept for 20 hours. The obtained solid was taken out and ground, and then placed in a tubular furnace for calcination at a temperature of 350°C for 6 hours. The obtained solid was ground and recorded as Example 4.

[0051] Comparative Example 1:

[0052] 111.2 g of ferrous sulfate heptahydrate, 56.8 g of sodium sulfate and 0.25 g of emulsifier were added to 500 mL of pure water. After complete dissolution, 3 g of single-layer graphene was added and mixed evenly.

[0053] After completion, it is placed at -40°C for low-temperature solidification, and then dried in a low-temperature vacuum. After keeping it for 24 hours, the obtained solid is taken out and ground, and then placed in a tubular furnace for calcination. The calcination temperature is 340°C and the calcination time is 6 hours. The obtained solid is ground and recorded as Comparative Example 1.

[0054] The same method was used to prepare sodium ion batteries using the graphene-coated sodium iron sulfate products of Examples 1 to 4 and Comparative Example 1, and their electrochemical properties were measured. The test voltage for the discharge capacity test was 2 to 4.5 V. Figure 3 This is the 0.1C charge-discharge capacity test curve for the sample in Example 1; the rate performance test was performed at 1C, 3C, and 5C (1C = 120 mAh / g) with a voltage range of 2.0 to 4.5V; the cycle performance test was performed at 3C for 500 cycles. The tests were performed using a constant current and constant voltage process for charging and a constant current process for discharging. The test results are shown in Table 1 below:

[0055] Table 1 Electrochemical performance test results of sodium ion batteries

[0056]

[0057] The results in Table 1 show that the 0.1C discharge capacity of the embodiment ranges from 97.93 to 100.07 mAh / g, the first charge capacity obtained at 1C is 80.56 to 86.06 mAh / g, the first charge capacity obtained at 3C is 76.98 to 83.23 mAh / g, and the first charge capacity obtained at 5C is 70.32 to 80.22 mAh / g, all of which are higher than the sample in Comparative Example 1. Therefore, compared with the comparative example, the graphene-coated sodium ferric sulfate product prepared by the method of the present invention can exert relatively better capacity, high rate performance and long-term stable cycle performance in sodium ion batteries.

[0058] In addition, in order to verify the prior art mentioned in the above background technology: a method for preparing a carbon-coated sodium ferric sulfate material, a carbon-coated sodium ferric sulfate material, and the yield of carbon-coated sodium ferric sulfate in a battery, several embodiments in its specification are used as comparative examples of the present invention as follows:

[0059] Comparative Example 2: Example 1 of CN116093292A specification

[0060] Comparative Example 3: Example 2a of CN116093292A specification

[0061] Comparative Example 4: Example 3b of CN116093292A specification

[0062] Comparative Example 5: Example 4a of CN116093292A specification

[0063] Table 2 Comparison of yields of Examples and Comparative Examples

[0064] This invention project Example 1 Example 2 Example 3 Example 4 Yield / % 93.1 92.3 94.5 93.6 Comparison of patent projects Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Yield / % 80.3 76.9 78.7 79.2

[0065] Obviously, the method in the prior art cannot achieve excellent yield. During the research process of the present invention, several other embodiments in the specification were reproduced many times, and the overall yield was around 75%, while the method of the present invention can reach a minimum of 92%. In addition, the present invention uses an emulsion instead of traditional pure water as the liquid phase, so that sodium ferric sulfate can be completely dissolved while the graphene powder can be more evenly dispersed; at the same time, a polymerization reaction is carried out in the emulsion to synthesize polyacrylic acid. The presence of carboxyl groups in the polymer can effectively improve the binding ability of sodium ferric sulfate and graphene, and due to the influence of polymer steric hindrance, the graphene-coated sodium ferric sulfate crystals after drying are smaller in size, more regular in morphology, and have a good coating effect.

[0066] The above are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by a person skilled in the art within the technical scope disclosed in the present invention should be included in the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be based on the scope of protection defined by the claims.

[0067] Any matters not described in detail in the present invention are well-known technologies to those skilled in the art.

Claims

1. A method for preparing a carbon-coated sodium ferric sulfate material, characterized in that: The specific steps include: S1. Add the emulsifier dropwise into pure water and disperse evenly; S2. Add ferrous sulfate heptahydrate and anhydrous sodium sulfate powder to the mixture obtained in S1 and disperse until the solid powder is completely dissolved; S3. Graphene is added to the mixture obtained in S2 and dispersed evenly; S4. The mixture obtained in S3 is heated to the preheating temperature and a polymerization initiator is added; S5. Acrylic acid was added dropwise to the mixture obtained in S4; S6. The mixture obtained in S5 was heated to the reaction temperature and kept warm until the reaction was fully cooled to room temperature; S7. The mixture obtained in S6 was freeze-dried and dried under vacuum at low temperature after solidification to obtain a solid; S8. Grind the solid obtained in S7, calcine it, and then grind it again to obtain a carbon-coated sodium ferric sulfate product.

2. The method for preparing a carbon-coated sodium ferric sulfate material according to claim 1, wherein: In step S1, the mass ratio of emulsifier to water is (0.0004-0.001):

1.

3. The method for preparing a carbon-coated sodium ferric sulfate material according to claim 1, wherein: In step S2, the mass ratio of ferrous sulfate heptahydrate to water is (0.22-0.25):1, and the molar ratio of ferrous sulfate heptahydrate to anhydrous sodium sulfate is 1:(0.5-2).

4. The method for preparing a carbon-coated sodium ferric sulfate material according to claim 1, wherein: In step S3, the type of graphene is one or more of single-layer graphene, double-layer graphene, and thick-layer graphene, and the mass ratio of graphene to ferrous sulfate heptahydrate is (0.02-0.08):

1.

5. The method for preparing a carbon-coated sodium ferric sulfate material according to claim 1, wherein: In step S4, the preheating temperature is 60-70° C., and the initiator is one of ammonium persulfate and potassium persulfate, and the mass ratio of ammonium persulfate to the emulsifier is 1:(2-3).

6. The method for preparing a carbon-coated sodium ferric sulfate material according to claim 1, wherein: In the step S5, acrylic acid is added dropwise using a peristaltic pump, the speed of the peristaltic pump is controlled at 3-5 rpm, and the mass ratio of acrylic acid to water is (0.01-0.015):

1.

7. The method for preparing a carbon-coated sodium ferric sulfate material according to claim 1, wherein: In step S6, the reaction temperature is 75-85° C., and the insulation time is 0.8-1.2 h.

8. The method for preparing a carbon-coated sodium ferric sulfate material according to claim 1, wherein: In step S7, the freeze-drying temperature is -60 to -40°C, and the low-temperature vacuum drying treatment time is 18 to 24 hours.

9. The method for preparing a carbon-coated sodium ferric sulfate material according to claim 1, wherein: In the step S8, a tubular furnace is used for calcination, the calcination temperature is 300-360° C., and the calcination time is 5-7 hours.

10. The method for preparing a carbon-coated sodium ferric sulfate material according to claim 1, wherein: The yield of the carbon-coated sodium ferric sulfate product prepared by the preparation method is 92-95%, and the graphene is evenly coated on the surface of the sodium ferric sulfate, and the microscopic morphology is spherical.

Citation Information

Patent Citations

  • Method for preparing carbon-coated sodium ferric sulfate material, carbon-coated sodium ferric sulfate material and battery

    CN116093292A

  • Lithium cobalt oxide positive electrode material compounded with graphene and preparation method thereof

    CN107579247A

  • Acrylic acid multipolymer, and preparation method and application of acrylic acid multipolymer in positive pole piece

    CN113372482A